Maternal endotoxin-induced fetal growth restriction in rats: Fetal responses in toll-like receptor - Banun Kusumawardani; Marsetyawan HNE. Soesatyo; Djaswadi Dasuki; Widya Asmara (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Porphyromonas gingivalis as a major etiology of periodontal disease can produce virulence factor, lipopolysaccharide/LPS, which is expected to play a role in the intrauterine fetal growth. Trophoblast at the maternal-fetal interface actively participates in response to infection through the expression of a family of natural immune receptors, toll-like receptor (TLR). Purpose: the aims of study were to identify endotoxin concentration in maternal blood serum of Porphyromonas gingivalis-infected pregnant rats, to characterize the TLR-4 expression in trophoblast cells, and to determine its effect on fetal growth. Methods: Female rats were infected with live-Porphyromonas gingivalis at concentration of 2 x 109 cells/ml into subgingival sulcus area of the maxillary first molar before and/or during pregnancy. They were sacrified on 14th and 20th gestational day. Fetuses were evaluated for weight and length. Endotoxin was detected by limulus amebocyte lysate assay in the maternal blood serum. The TLR-4 expression in trophoblast cells was detected by immunohistochemistry. <span style="font-family: Tribune-Bold; font-size: